Echoes of Aggression. The Gendered Impact of School Bullying on the Well-Being of Victims and Witnesses - Till Stefes (Social Indicators Research, 2025)
This study examines the impact of bullying victimization and witnessing classroom bullying on adolescents' subjective well-being (SWB) and whether these effects are independent of each other. Effects of bullying on uninvolved bystanders are yet to be explained in sociology. The article presents evidence and explanation of this effect for different forms of bullying, introducing echo-effects of aggressive behaviour. Using multilevel regression analysis on data from 121 classrooms, the findings show that both victimization and witnessing bullying significantly harm SWB, with girls being more affected than boys. The study employs a robust, multi-dimensional index to measure SWB, collected among secondary schools in Germany. Results indicate that bullying experiences vary by gender, with boys facing more physical violence and girls more often targeted indirectly or online, aligning with prior research on the matter. While patterns vary, effects seem to be similar. Significantly negative impact on SWB underscores the need for effective interventions at the classroom level to support both victims and witnesses, highlighting the importance of addressing the complex dynamics within school environments and considering the distinct experiences of different gender groups.
Keywords: 300; Bullying; Victimization; Subjective well-being; Peer relations; Violence; School